LoRa Radius Coverage Map on Urban and Rural Areas: Case Study of Athens’ Northern Suburbs and Tinos Island, Greece - Spyridon Mitropoulos; Vasilios A. Orfanos; Dimitrios Rimpas; Ioannis Christakis (Engineering Proceedings)
As the use and development of Internet of Things is very popular nowadays, one of the most widespread ways of exchanging data from such arrangements is the use of the LoRa network. One of the advantages offered by this technology is the ability to provide low power consumption as well as wide wireless coverage in an area. Although in research, there are references regarding the coverage radius of a geographical area, differences can be detected between urban (cities) and rural (countryside) areas, as in the latter, there are no dense structures nor radio signal noise inside the operating frequency spectrum of LoRa. Thus, results are expected to be better in rural areas than urban areas. Especially in an urban area, apart from the signal noise caused by other LoRa devices (either commercial or private), the coverage varies according to the placement of the LoRa station inside a building, which is related to the height at which the gateway is placed in another building. In this work, the LoRa radio coverage study is presented in a radius of 2 km both in an urban and a rural environment using only one LoRa gateway. To better capture the coverage, LoRa stations are placed on every floor of the selected buildings periodically. The results show the difference in coverage between urban and rural areas which is related to radio signal noise. Furthermore, significant changes in the coverage map in urban areas can be observed, directly related to the installation height of the LoRa station. With the understanding of these variations in LoRa network performance in different environments, informed decisions can be made regarding the deployment of such networks, optimizing their efficiency and ensuring seamless data transmission in both urban and rural settings.